Effects of leadership style on coach-athlete relationship, athletes’ motivations, and athlete satisfaction - Jin, Hao; Kim, Seungmo; Love, Adam; Jin, Yun; Zhao, Jie (Frontiers in Psychology, 2022)
Introduction The current study investigated the impacts of autocratic and democratic leadership styles on the coach-athlete relationship, athletes’ motivations, and athlete satisfaction. Methods Survey data were collected from 298 student-athletes (male = 157; 52.7%, female = 141; 47.3%) from 20 different Chinese collegiate sports. The Structural Equation Model was used to test the hypothesized model. Results The results indicated democratic leadership had a direct positive influence on the coach-athlete relationship, while autocratic leadership had no direct effect. Both leadership styles did not influence autonomous motivation. The coach-athlete relationship, meanwhile, had a full mediation effect between democratic leadership and athletes’ motivation and satisfaction. In addition, autonomous motivation had a partial mediation effect between the coach-athlete relationship and athlete satisfaction. Discussion Ultimately, the findings of the current study underscore the need for coaches and administrators to understand the impact of different leadership styles and highlight the importance of democratic leadership in improving athletes’ psychological outcomes.